6(-2-x)=-5(x+3)

Simple and best practice solution for 6(-2-x)=-5(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(-2-x)=-5(x+3) equation:


Simplifying
6(-2 + -1x) = -5(x + 3)
(-2 * 6 + -1x * 6) = -5(x + 3)
(-12 + -6x) = -5(x + 3)

Reorder the terms:
-12 + -6x = -5(3 + x)
-12 + -6x = (3 * -5 + x * -5)
-12 + -6x = (-15 + -5x)

Solving
-12 + -6x = -15 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-12 + -6x + 5x = -15 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-12 + -1x = -15 + -5x + 5x

Combine like terms: -5x + 5x = 0
-12 + -1x = -15 + 0
-12 + -1x = -15

Add '12' to each side of the equation.
-12 + 12 + -1x = -15 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = -15 + 12
-1x = -15 + 12

Combine like terms: -15 + 12 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| 5x-4-3x=14 | | -4=n | | 4e^3x+2=110 | | 10(s-4)=-132 | | 4e^3x+2=20 | | 10(s-4)=3 | | 10/3(10) | | 4e^3x-2=110 | | 2/3=7/x-4 | | -7-15x=23 | | 0.2+x=3 | | 2x+3y+6z=98 | | 60x=-32 | | 82=14+2x | | -5(7x+10)=-295 | | 3/4p=114 | | 26/x=13/8 | | y=x^2-17/2 | | 2c+5=3c | | 17x-4=4(4x+5)-16 | | 2c+5=8c | | 4c+6=6c | | 4c+6=6 | | 10x(8x^3+1)=0 | | log(x/5)=3 | | x+9=8+4 | | 32-5q=-100 | | 40x+65=325 | | x^2=4y-3+7 | | x+1=75 | | 2z-7=26 | | 6w-8=4(2w+5) |

Equations solver categories